Perbedaan Pengetahuan dan Sikap WUS Tentang Skrining IVA Setelah Diberikan Penyuluhan dengan Media Video - Putri, Ni Luh Putu Andhika Wilyana; Wirata, I Nyoman; Armini, Ni Wayan (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2025)
Cervical cancer occupies the top position among various types of cancer that cause death in women throughout the world. Cervical cancer can be detected early using the acetic acid visual inspection method. This study aims to determine differences in knowledge and attitudes of women of childbearing age regarding acetic acid visual inspection screening before and after being given counseling using video media in Beraban village. The type of research in this research was pre-experimental with a one group pretest-posttest design with a sample size of 36 people. The sampling technique in this research was non-probability sampling, purposive sampling type. The data collection technique used was a questionnaire. The data analysis used were univariate and bivariate analysis. From the research results, it was found that there was a difference in the knowledge of women of childbearing age regarding acetic acid visual inspection screening before and after being given video counseling with a value of p 0.00 < 0.05. The suggestions from this research were: For women of childbearing age to actively seek information, especially using video media, to find out about acetic acid visual inspection examinations and carry out acetic acid visual inspection examinations. For research sites to use videos to provide education about acetic acid visual inspection examinations so that they can increase women of childbearing age knowledge about acetic acid visual inspection examinations. Future researchers were expected to develop this research to provide innovation and dig deeper into the factors that influence women of childbearing age knowledge and attitudes about acetic acid visual inspection screening.